Formation of indium–tin oxide ohmic contacts for β-Ga2O3. (26th October 2016) - Oshima, Takayoshi; Wakabayashi, Ryo; Hattori, Mai; Hashiguchi, Akihiro; Kawano, Naoto; Sasaki, Kohei; Masui, Takekazu; Kuramata, Akito; Yamakoshi, Shigenobu; Yoshimatsu, Kohei; Ohtomo, Akira; Oishi, Toshiyuki; et al.
Abstract: Sputter-deposited indium–tin oxide (ITO) electrodes became ohmic contacts for unintentionally doped β-Ga2 O3 (010) substrates with a carrier concentration of 2 × 10 17 cm −3 after rapid thermal annealing in a wide range of annealing temperatures of 900–1150 °C. The formation of an ohmic contact is attributed to interdiffusion between ITO and β-Ga2 O3, as evidenced by the results of transmission electron microscopy and energy-dispersive X-ray spectroscopy. The interdiffusion decreases the band gap and increases the donor concentration of β-Ga2 O3 at the interface, and forms an intermediate semiconductor layer desirable for carrier transport. The ITO ohmic contact is particularly useful for future β-Ga2 O3 devices operated at high temperatures.